The Implementation Strategy of War Ethics Training for Indonesian National Army (TNI) Members - Andi Ichsan; Educ Permadi Eko Putro Basuki; Dinand Tumpak Willians; Wahyu Ramadhanus Suryawan; Tarsisius Susilo (International Research and Development for Human Beings (IRDH), 2025)
The ethics of war is a set of moral principles that govern actions in armed conflict, aiming to reduce atrocities and protect human rights. The purpose of this study is to determine the strengths, weaknesses, threats, and opportunities in the implementation of war ethics training for members of the Indonesian National Army, as well as to formulate a strategy for the implementation of war ethics training for members of the Indonesian National Army. The results of the study found that there are 5 factors of strengths, weaknesses, opportunities, and threats in the preparation of war ethics training strategies. The biggest strength factor is that war ethics have received attention from TNI members in the implementation of their duties and Indonesia has become a country that upholds humanitarian law and war ethics in a free and active foreign policy. Meanwhile, the biggest weakness factor is that war ethics are aspects of values that are abstract and difficult to implement in the field. The greatest opportunity factor is that the development of information technology allows war ethics to be prioritized in military training. Meanwhile, the biggest weakness factor is that the indicators for measuring military personnel's understanding of war ethics are still biased. This study provides recommendations in the form of 7 strategies that can be implemented to develop war ethics training for TNI members, namely (1) strengthening the study of war ethics, (2) creating avenues for cooperation with other institutions regarding the development of the war ethics training curriculum, (3) facilitating discussions with the National Human Rights Commission, (4) initiating collaborative efforts to write reference books on war ethics, (5) establishing technical policies within the military environment regarding war ethics training, (6) encouraging the Government of the Republic of Indonesia to take a strategic role as a pioneer in the implementation of war ethics. (7) develop theoretical and practical concepts about the compatibility of the implementation of military values and ethical values.